The PRAME family of cancer testis antigens is essential for germline development and gametogenesis - Chandlar Kern; Ming-Yao Yang; Wansheng Liu (2021)
Abstract Preferentially expressed antigen in melanoma (PRAME) belongs to a group of cancer/testis antigens that are predominately expressed in the testis and a variety of tumors, and are involved in immunity and reproduction. Much of the attention on PRAME has centered on cancer biology as PRAME is a prognostic biomarker for a wide range of cancers and a potential immunotherapeutic target. Less information is available about the PRAME family’s function (s) during gametogenesis and in the overall reproduction process. Here, we review the current knowledge of the PRAME gene family and its function in germline development and gametogenesis. Members of the PRAME family are leucine rich repeat proteins, localized in nucleus and cytoplasm, with multifaceted roles in germ cells. As transcriptional regulators, the PRAME family proteins are involved in germline development, particularly in the maintenance of embryonic stem cell pluripotency, development of primordial germ cells, and differentiation/proliferation of spermatogenic and oogenic cells. The PRAME family proteins are also enriched in cytoplasmic organelles, such as rough endoplasmic reticulum, Golgi vesicle, germinal granules, centrioles, and play a role in the formation of the acrosome and sperm tail during spermiogenesis. The PRAME gene family remains transcriptionally active in the germline throughout the entire life cycle and is essential for gametogenesis, with some members specific to either male or female germ cells, while others are involved in both male and female gametogenesis. A potential molecular mechanism that underlies the function of PRAME, and is shared by gametogenesis and oncogenesis is also discussed.